The Influence of Hedonic Motivation, Perception of Online Prices, Access To Information, And Online Trust Towards Attitude And Purchase Intention on E-Commerce Platform - Sugijono, Vincentius Malvin; Pratomo, Luki Adiati (Green Publisher Indonesia, 2024)
This research is aimed to analyze the influence of hedonic motivation, perception of online prices, access to information, and online trust towards attitude and purchase intention on e-commerce platform. This study used primary data in the form of questionnaires from 190 respondents which were distributed non-probabilistically to consumers who used e-commerce services more than three times in the last 6 months in the period Ocotber-November 2023. Hypothesis was analyzed with SEM using AMOS 21. Research finding shows that hedonic motivation, perception of online prices, access to infroamtion have positive effect on attitude. However, online trust does not have positive effect on attitude. Then, attitude has a positive effect on purchase intention. The managerial implication of this research is an evaluation for e-commerce to improve consumer attitudes and purchase intention.